DEVELOPMENT OF A LEARNING MODULE BASED ON LOCAL WISDOM OF THE SASAK TRIBE ON FIFTH GRADE IN SOCIAL SCIENCE SUBJECT AT SDN 22 AMPENAN - Rasya, Ghudaifa; Tahir, Muhammad; Oktaviyanti, Itsna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research aims to produce a product in the form of a learning module based on the local wisdom of the Sasak Tribe, find out the steps for developing the module, and determine the feasibility of a learning module based on the local wisdom of the Sasak Tribe in social studies material for fifth-grade students at SDN 22 Ampenan. This type of research is Research and Development (R&D) using the ADDIE development model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at SDN 22 Ampenan with ten fifth-grade students as subjects. Data collection tools use questionnaires or questionnaires. The steps in developing a module are: 1) Analysis: perform performance analysis and analysis of student needs; 2) Design: design the module from cover to bibliography, determine KD, Indicators, Learning Objectives, materials, and activity evaluation; 3) Development: the module that has been designed is printed, validated by material experts and media experts then revised according to suggestions, 4) Implementation: the module is applied to students to see the students' response in using the module, 5) Evaluation: evaluation is carried out in the form of tests on participants students to see the students' understanding of the material. The results of research and development of learning modules based on local wisdom of the Sasak tribe in the fifth-grade social studies material show that it is very suitable for use in the learning process; this is based on the validation results of media experts at 77.64% (feasible), material experts at 93.6% (very feasible), and the student response was 81.38% (very feasible).